Integrated strato-tectonic, U-Pb geochronology and metallogenic studies of the Oudalan-Gorouol volcano-sedimentary Belt ( OGB) and the Gorom-Gorom granitoid terrane (GGGT), Burkina Faso and Niger, West Africa - Tshibubudze, Asinne (My University, 2015)
The Palaeoproterozoic Baoulé-Mossi domain of the West African Craton in northeastern Burkina Faso hosts numerous gold deposits such as Essakane and Tarpako. Integrated strato-tectonic, geophysical, geochemical, geochronological, regional stratigraphic framework and metallogenic studies of the Oudalan-Gorouol volcano-sedimentary Belt and the Gorom-Gorom Granitoid Terrane have provided new insight into the geotectonic evolution of the northeastern part of Burkina Faso. This work outlines the structural context and architecture necessary for forming these deposits. In this work, a new strato-tectonic model is proposed for the area by integrating field data and geophysical, geochemical, and geochronological data. The integrated data highlights and characterizes the setting of the Essakane gold mine and gold camp relative to the location of other regional gold deposits, metamorphosed Birimian Supergroup, intrusive rocks and shear zones. Structural, geochemical and geochronological analyses have helped to clarify the geological evolution of the Oudalan-Gorouol volcano-sedimentary Belt and the Gorom-Gorom Granitoid Terrane during the Tangaean (D1) and Eburnean (D2) orogenies through to the Wabo Tampelse Event (D3). Further to these, zircon U-Pb geochronology data have demonstrated that the Oudalan-Gorouol volcano-sedimentary Belt and the Gorom-Gorom Granitoid Terrane represent some of the oldest outcropping geology in the Palaeoproterozoic Baoulé-Mossi domain recognised to date. The geochronology and geology suggest that the basement or a pre- Birimian crust to the Birimian Supergroup may be found in the northeast of Burkina Faso. The Eburnean Orogeny in northeastern Burkina Faso is preceded by two phases of deformation (D1-x and D1), and two phases of magmatism. The first, D1-x, is associated with the emplacement of the Dori Batholith at the onset of D1 (2164 – 2141 Ma). D1 ductile-brittle deformation formed F1 folds and discrete high-strain mylonite zones that deformed the Oudalan- Gorouol volcano-sedimentary Belt and the Gorom-Gorom Granitoid Terrane during a southwestdirected palaeo-principal compressive stress. The pre-Birimian to Birimian supracrustal rocks and intrusions were regionally metamorphosed during D1 to greenschist to amphibolite facies with development of mineral assemblage of quartz-chlorite-muscovite ± chloritoid to biotite-potash feldspar ± hornblende. D1 is also associated with volcanic arc type calc-alkaline magmatism, producing TTGs enriched in heavy rare earth elements. The Eburnean Orogeny (2130 – 1980 Ma) is characterised by northwest-southeast shortening; it was followed by north-northwest - south-southeast shortening with development of northeast trending sinistral strike-slip faults and shears. D2 brittle-(ductile) deformation is manifested by refolding of F1 by northeast-trending F2, and development of a pervasive northeast-trending S2 to S2-C foliation. Metamorphic grade attained greenschist facies during D2, with development of mineral assemblage of quartz-chlorite-muscovite ± actinolite. The Wabo Tampelse (D3) deformation event is brittle in character and does not significantly affect the regional geological architecture in the study area.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2015.
Keywords: Geology--Structural.; Sedimentation and deposition.; Geochemistry.; Metallogeny.; Geological time.